Evaluating PT Unilever Indonesia Financial Performance amid Consumer Boycotts Using the DuPont Model - Arifah, Aida Nur (Journal of Banks and Financial Institutions, 2026)
Objective: This study analyzes the financial performance of PT Unilever for the 2021–2023 period in response to of the impact of the Boycott, Divestment, and Sanctions (BDS) movement arising from the Israel–Palestine conflict, using the DuPont System method. Research Design & Methods: This study adopts a quantitative descriptive approach using secondary data derived from the company’s financial statements, including balance sheets and income statements. The analysis employs the DuPont System, consisting of Net Profit Margin (NPM), Total Asset Turnover (TATO), and Return on Investment (ROI), to evaluate financial performance comprehensively. Findings: The results indicate that PT Unilever’s financial performance fluctuated over the observed period, improving in 2022 but declining significantly in 2023. This deterioration is reflected in decreasing NPM, TATO, and ROI values, suggesting reduced operational efficiency and profitability. Contributions: This study contributes to the literature on financial performance analysis using the Du Pont System and offers an additional perspective on the impact of external factors, specifically, consumer boycott movements on the performance of multinational companies. Novelty: The novelty of this study lies in integrating financial performance analysis with a global socio-political phenomenon, namely the BDS movement, which has rarely been explored in corporate finance studies in Indonesia